Electrohydraulic Tentacle Actuators: Rapid 3D Printing of Electrohydraulic (HASEL) Tentacle Actuators (Adv. Funct. Mater. 40/2020). (2nd October 2020) - O'Neill, Maura R.; Acome, Eric; Bakarich, Shannon; Mitchell, Shane K.; Timko, Julia; Keplinger, Christoph; Shepherd, Robert F.
Abstract : In article number 2005244, Robert F. Shepherd and co‐workers introduce a comprehensive multi‐material system and fabrication route for the design and manufacture of soft, electrohydraulic actuators. The actuation and self‐sensing capabilities of the capacitive modules are demonstrated. Moreover, they employ 3D printing to pattern dense arrays of these capacitive actuators to form a synthetic muscular hydrostat capable of multi‐dimensional motion.